Improving the content of high value compounds in Nordic Desmodesmus microalgal strains. (September 2022) - Mehariya, Sanjeet; Plöhn, Martin; Leon-Vaz, Antonio; Patel, Alok; Funk, Christiane
Graphical abstract: Highlights: Nordic microalgae produce compounds of high value when exposed to abiotic stress. Light stress stimulates carotenoid production up to 44 mg L −1 in Desmodesmus sp. Combined light and salt stress enhanced the lipid content by 43% of DW. Nordic microalgae grown in various wastewaters can produce carotenoids and lipids. Abstract: Nordic Desmodesmus microalgal strains (2–6) and (RUC-2) were exposed to abiotic stress (light and salt) to enhance lipids and carotenoids. The biomass output of both strains increased by more than 50% during light stress of 800 μmol m −2 s −1 compared to control light. The biomass of Desmodesmus sp. (2–6) contained most lipids (15% of dry weight) and total carotenoids (16.6 mg g −1 ) when grown at moderate light stress (400 μmol m −2 s −1 ), which further could be enhanced up to 2.5-fold by salinity stress. Desmodesmus sp. (RUC-2) exhibited maximal lipid (26.5%) and carotenoid (43.8 mg L −1 ) content at light intensities of 400 and 100 μmol m −2 s −1, respectively. Salinity stress stimulated lipid accumulation by 39%. Nordic Desmodesmus strains therefore are not only able to tolerate stress conditions, but their biomass considerably improves under stress. These strains have high potential to be used in algal bio-factories on low-cost medium like Baltic seawater.